Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA Materi Penguasaan Konsep Tekanan Melalui Metode Discovery Learning di Kelas VIII SMP Negeri 2 Kota Bogor - Juwitasari, N. Tita (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
IMPROVING STUDENT LEARNING OUTCOMES IN SCIENCE SUBJECT MATERIAL MASTERY OF THE CONCEPT OF PRESSURE THROUGH THE DISCOVERY LEARNING METHOD IN GRADE VIII JUNIOR HIGH SCHOOLS (SMP NEGERI 2 KOTA BOGOR) This research departs from a phenomenon that occurred in class VIII semester II of SMP Negeri 2 Bogor for the 2021/2022 Academic Year, that there is still a low understanding and learning outcomes of students in learning Science about Pressure. Therefore a teacher needs to consider the application of the Discovery Learning learning model so that it can improve student learning outcomes. the process of increasing student learning outcomes in the Science subject under Pressure through the application of the Discovery Learning learning model, (3) Measuring the magnitude of the increase in student learning outcomes in the Science subject under Pressure through the application of the Discovery Learning learning model. The results of this study indicate that using the Discovery Learning learning model can be a fun learning variation for students so that it is proven to improve student learning outcomes in class VIII semester II SMP Negeri 2 Bogor in the 2021/2022 academic year. Before using the Discovery Learning learning model the average and learning completeness were 67.50 and 50.00% then there was an increase after using the Discovery Learning learning model to 74.83 and 70.59% in cycle I, and an increase again to 83.50 and 100 % in cycle II. From the description above, it shows that using the Discovery Learning learning model adapted to learning materials can create a pleasant atmosphere so that there is an increase in student learning outcomes. Therefore, researchers suggest that the application of the Discovery Learning model can be socialized as an alternative in learning science in schools within the Bogor City Education Office.